MSME Performance: Financial Information System, Work Productivity, and E-commerce - Andi Arifwangsa Adiningrat; Idrawahyuni Idrawahyuni; Rustan Rustan; Yuyu Ruhayu (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2023)
This study aims to identify and analyze financial information systems, work productivity, and e-commerce on the performance of MSMEs. The approach in this study used a qualitative approach. The sources of informants were seven SMEs in the fields of food and clothing in Makassar City. Data collection techniques were carried out by interviewing informants and literature studies. The steps for the analysis technique used were data reduction, data presentation, and conclusion. The study results show that work productivity and e-commerce effectively support MSME activities to improve MSME performance. At the same time, the financial information system has not been implemented optimally, so MSME performance has not increased optimally. Some MSMEs have done computerized financial bookkeeping, but some MSMEs still do financial bookkeeping manually due to a lack of managerial knowledge and skills. The implications of this research are very important to help MSMEs identify opportunities and challenges by having a good financial information system that can optimize financial management, good productivity, and utilize e-commerce in their business.